NEUROLINGUISTIC APPROACH AS A METHODOLOGICAL PROBLEM - Togayeva Umida Shavki kizi (Western European Studies, 2024)
this article provides the most general information about the new field of linguistics - neurolinguistics, general objects and problems studied by this field, as well as scientific information about the history, present day and sources of the direction. Describes the neurolinguistic approach, its emergence, current issues of teaching based on the neurolinguistic approach, the possibilities of using the neurolinguistic approach in pedagogy, the specific features of using best practices in the teaching process.
Keywords: neurolinguistics; neurolinguistic approach; brain